Maria Zarębińska-Broniewska (1904–1947). Aktorka, pisarka, więzień Oświęcimia - Uljasz, Adrian (Przegląd Nauk Historycznych, 2014)
Maria Zarębińska-Broniewska, the wife of Władysław Broniewski, a poet, was an actress, performing during the period of „2nd Republic” on stages of Wilno, Radom, Katowice and Warszawa. She also gained film experience by playing a few small parts in Polish films. At the outset of World War II she was performing in Lviv, then under Soviet occupation. Later she resided in the area occupied by Germans and was the prisoner of Auschwitz and Ravensbrück–Altenburg camps. After the liberation she performed in Polish Army Theater in Lodz. She died as a result of health problems caused by her stay in camps. She left us her literary work, of high historic, esthetic and educational value, published after World War II, such as a children’s book Children of Warszawa, a novel on Holocaust and the support provided by Poles to persecuted population, and Stories from Auschwitz, with autobiographic themes, addressed to adults.